1998
DOI: 10.1002/(sici)1520-667x(1998)10:3<249::aid-mcs2>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized evaporative light scattering detector for application with packed microcolumn high‐performance liquid chromatography

Abstract: Ž. Abstract: A miniaturized evaporative light scattering detector ELSD compatible Ž . with packed microcolumn high-performance liquid chromatography HPLC has been developed. In such a detector, it is particularly important that an efficient nebulization of the column effluent is achieved. Therefore, the geometry of the nebulizer has been optimized. Detector performance was demonstrated for ace-tonitrile᎐acetone at 5᎐100 L min y1 as mobile phase, a packed microcolumn, 0.7 mm i.d. was used. Isocratic and gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…It follows that when gas flow rate is constant, to achieve the supersonic condition, the annular gap should be extremely narrow. Then nebulization can be performed efficiently at a relatively low volumetric gas flow rate . Likewise, the lower the mobile phase flow rate, the smaller must be the annular gap of the nebulizer nozzle to accommodate the low level flow rate of the mobile phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows that when gas flow rate is constant, to achieve the supersonic condition, the annular gap should be extremely narrow. Then nebulization can be performed efficiently at a relatively low volumetric gas flow rate . Likewise, the lower the mobile phase flow rate, the smaller must be the annular gap of the nebulizer nozzle to accommodate the low level flow rate of the mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…Greibrokk also demonstrated an interface of microcolumn supercritical fluid chromatography (SFC) to ELSD . A miniaturized ELSD for application with packed microcolumn HPLC or SFC was reported by Andersson et al They found that a makeup solvent (hexane at 30 μL/min) assisted in proper effluent nebulization, while the flow rate of the mobile phase was 5–100 μL/min, too great for CLC or pCEC. Recently, Gaudin et al adapted a commercial detector to micro and CLC, based on the predicted size of the nebulized droplets via the Nukiyama and Tanasawa empirical equation .…”
mentioning
confidence: 99%
“…Απαζηεί ιζηνή ηαηακάθςζδ δζαθοηχκ ηαζ επζπθέμκ είκαζ ζοιααηή ιε ζοζηήιαηα ακζπκεοηή θαζιαημιέηνμο ιαγχκ. Ζ ζφγεολδ ημο ELSD ιε έκα ηέημζμ ζφζηδια ηαηέζηδ δοκαηή ιεηά απυ ηνμπμπμίδζδ ζηδκ ηορεθίδα εηκέθςζδξ, χζηε κα νοειίγεηαζ ιε αηνίαεζα δ ηαηεφεοκζδ ημο εηθμφζιαημξ ζε ζπέζδ ιε ημ αένζμ εηκέθςζδξ, ηαζ ιε ηαοηυπνμκδ ιεηααμθή ηςκ δζαζηάζεςκ ημο εαθάιμο ελάηιζζδξ, μ μπμίμξ βίκεηαζ ιζηνυηενμξ ζε ιήημξ ηαζ δζάιεηνμ [63][64][65] .…”
Section: ύδεπμε ηνπ Elsd κε ζπζηήκαηα κηθξν-υξσκαηνγξαθίαοunclassified